Halal Food di Era Revolusi Industri 4.0: Prospek dan Tantangan - Achmad Fawaid (Universitas Negeri Jakarta, 2019)
The rapid change of industrial technology has increased some artificial intelligence in many aspects, including halal food. This paper seeks to find out the halal food industry in the era of the Industrial Revolution 4.0 and its impact on the existence of halal food in Indonesia. During Industrial Revolution 4.0, it is easy to manage halal food in terms of production or marketing process through sophisticated machine, complete laboratorium, modern halal valley, or artifical intelligences based applications. All of these aspects contribute to the halal food industries in Indonesia, since they are possible to be more popular, boarder in marketing, more effective in production, quicker in menu, more competitive in market. The halal food industry, in fact, has to be charged in global competitivenes.